PENINGKATAN KUALITAS KESEHATAN MASYARAKAT ERA PANDEMIC COVID-19 MELALUI PEMANFAATAN TANAMAN OBAT KELUARGA SEBAGAI SUMBER IMMUNOMODULATOR - Sunandar Ihsan; Yamin Yamin; Muhammad Handoyo Sahumena; Wa Ode Sitti Zubaydah; Arfan Arfan (Universitas Halu Oleo, 2022)
Coronavirus Diseases 2019 (COVID-19) is a disease caused by a new coronavirus strain (SARS-CoV-2) which then mutates into various variants including the omicron variant, alpha variant, beta variant, and gamma variant. Where, transmission will pose a high risk when the body's immunity is low. The purpose of this activity is to provide information on various